Intention to Sell on E-Marketplace: Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Price Value - Leo Agung Puri Bowo Laksono; Gede Sri Darma (Quantitative Economics and Management Studies, 2024)
The rapid growth of electronic marketplaces in Indonesia, coupled with government encouragement for businesses, necessitates a thorough understanding of sellers' adoption factors. This study investigates the influences on e-marketplace application adoption among active Indonesian sellers, incorporating gender, age, and experience as moderating variables. Employing SMARTPLS4 and PLS SEM analysis, the research identifies significant impacts of effort expectancy, performance expectancy, and price value on e-marketplace selling behavior. Contrarily, facilitating conditions and social influence show no effect. Age moderation significantly influences effort expectancy and price value, emphasizing the importance of tailored strategies for different age groups. Gender and experience, however, do not significantly moderate the results. Sellers' expectations emphasize the need for stakeholders to ensure fairness in online transactions, urging the government to establish appropriate e-marketplace regulations, aligning with sellers' needs for a thriving digital marketplace ecosystem.